Towards sustainable logistics in India: Forecasting freight transport emissions and policy evaluations - Mishra N.B.; Pani A.; Bansal P.; Sourava Mohapatra S.; Sahu P.K. (My University, 2025)
This paper forecasts the growth of freight transport emissions in India's trucking sector until 2050. We use the ARIMAX time series model to project the commercial vehicle population under various economic growth scenarios. CO2 emissions are estimated using emission factors, distance traveled, and the projected commercial vehicle population. We use the validated forecasting model to investigate how emissions can be curbed through vehicle scrappage policies or fleet electrification to realign with the 2015 Paris Agreement's targets. Compared to the business-as-usual (BAU) scenario, 10-year and 15-year vehicle scrappage policies are estimated to reduce freight emissions by 6–11% and 1–2%, respectively. Fleet electrification has more pronounced effects as it results in a 35% and 70% reduction in carbon emissions for heavy and light goods vehicles in 2050, respectively, compared to the BAU scenario. These findings provide crucial insights for devising policies to mitigate greenhouse gas emissions in India's trucking industry. © 2024 Elsevier Ltd